2002
DOI: 10.3168/jds.s0022-0302(02)74356-7
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Method for Prediction of Cheese Yield

Abstract: Theoretical cheese yield can be estimated from the milk fat and casein or protein content of milk using classical formulae, such as the VanSlyke formula. These equations are reliable predictors of theoretical or actual yield based on accurately measured milk fat and casein content. Many cheese makers desire to base payment for milk to dairy farmers on the yield of cheese. In small factories, however, accurate measurement of fat and casein content of milk by either chemical methods or infrared milk analysis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 7 publications
2
30
3
Order By: Relevance
“…This point was further discussed regarding the exact major fraction to be used in the calculations (Emmons and Modler, 2010). Indeed, using such equations on milk coming from uninfected animals during the major part of their lactation, as well as using bulk tank milk resulted in good agreement between experimental and calculated results (van den Berg et al, 1996;Melilli et al, 2002;Emmons et al, 2003). However, a certain number of animals in a herd at each point of time are infected or are at certain physiological conditions that lead to production of milk that deviates from what is accepted as 'normal milk' (Pitkä lä et al, 2004;Sampimon et al, 2009;Leitner et al, 2011a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This point was further discussed regarding the exact major fraction to be used in the calculations (Emmons and Modler, 2010). Indeed, using such equations on milk coming from uninfected animals during the major part of their lactation, as well as using bulk tank milk resulted in good agreement between experimental and calculated results (van den Berg et al, 1996;Melilli et al, 2002;Emmons et al, 2003). However, a certain number of animals in a herd at each point of time are infected or are at certain physiological conditions that lead to production of milk that deviates from what is accepted as 'normal milk' (Pitkä lä et al, 2004;Sampimon et al, 2009;Leitner et al, 2011a).…”
Section: Resultsmentioning
confidence: 99%
“…The economical profitability of the industry has always been based on the qualities of the bulk milk as tested by the dairy laboratories. Cheese yield is one of the major factors influencing dairy economics and is usually calculated according to various equations (Emmons and Binns, 1990;Barbano et al, 1991;Emmons et al, 1993 andMelilli et al, 2002). The objective of producing the appropriate quality milk for cheese production has been achieved through genetic management and nutrition improvements, which have led to higher cheese yields from the bulk milk tank.…”
Section: Introductionmentioning
confidence: 99%
“…Cheese yield and curd firmness are determined by milk protein concentration and casein number [CN; 25,35]. As discussed above and shown previously [33], the reduction of the milk protein yield was simultaneously caused by low energy supply and hypoxia.…”
Section: Factors Explaining the Effect Of High Altitude Grazing On MImentioning
confidence: 99%
“…For volume calculation (L) of raw milk necessary to process one kg of RC, we also used an adaptation of Van Slyke's formula (Emmons and Modler, 2010;Melilli et al, 2002) replacing the term 'C 50j -LC i ' by 'RP i *P 50j ' as shown below:…”
Section: Earnings Before Taxes Interest Depreciation and Amortizatimentioning
confidence: 99%
“…To determine the milk volume required to produce each kg of MS, MC, MB, MF, PB, SP and RC cheeses, we used the prediction equation for cheese production of Van Slyke adapted (Emmons and Modler, 2010;Melilli et al, 2002) as follows:…”
Section: Restrictions and Equationsmentioning
confidence: 99%